Value of Clinical Tests in Diagnosing Anterior Cruciate Ligament Tears: What Is New? - Nguyen, Long Thanh; Truong, Son Van; Nguyen, Uyen Thi Phuong (Revista Brasileira de Ortopedia, 2025)
To investigate the value of clinical diagnostic tests for diagnosing anterior cruciate ligament (ACL) tears with the anterior drawer, Lachman, Pivot-shift, lever sign, and Forced Active Buckling (FAB)-sign tests.A cross-sectional study was conducted on 165 knee injury patients who were indicated for knee arthroscopy from January to December 2022. The clinical examination results were compared with the procedure's gold standard to determine the value of clinical diagnostic tests.The sensitivity and specificity values, respectively, were anterior drawer test: 77.5% and 86.1%; Lachman: 87.6% and 88.9%; Pivot-shift: 65.9% and 94.4%; Lever sign: 93.8% and 94.4%; and FAB sign: 81.4% and 97.2%.There are various clinical diagnostic tests for ACL tears. The Lever sign is a useful clinical test for physicians to examine and diagnose this condition.
Keywords: anterior cruciate ligament injuries; knee injuries; meniscus; rupture